Healthcare Practitioners’ perspectives on paediatric burns management at Korle Bu Teaching Hospital, Ghana - Alberta A. Rockson; Natalie Benjamin-Damons; Sonti Imogene Pilusa (Burns Open)
Background: Paediatric burns pose significant challenges in healthcare management. Paediatric burns require specialized care due to the distinct anatomical and physiological characteristics of children, which make them more vulnerable to complications. In resource-limited settings like Ghana, the absence of adequate supplies and standardized protocols can exacerbate these challenges, necessitating the need for a comprehensive understanding of the perspectives of healthcare practitioners involved in their care.Study Objective.To explore healthcare practitioners’ perspectives on paediatric burns management at a tertiary hospital, Ghana, covering current practices, barriers, impacts on patients and families, and recommendations for improvement. Methodology: This study employed a qualitative research approach utilizing Focus Group Discussion (FGD) with 15 participants from various disciplines, including Plastic Surgery, Medicine, Anaesthetics, Physiotherapy, Occupational Therapy, Dietetics, Nursing, Pharmacy, Clinical Psychology, Public Health Nursing and. Laboratory Scientist. Participants were recruited through a convenience sampling technique. The discussion lasting approximately 90 min, were audio recorded, and facilitated by a discussion guide based on existing literature. The audio recordings were transcribed verbatim, and the transcripts were compared with handwritten notes for accuracy. The final transcribed data were coded and analyzed using thematic content analysis to identify recurring themes and patterns. Results: Findings revealed four primary themes: strengths of current practices (multidisciplinary approach, experienced practitioners), barriers (lack of formal protocols, infrastructure limitations, financial burdens), contextual factors influencing burn care (psychological trauma, inadequate support, socio-cultural beliefs and socioeconomic status), and recommendations for enhancing burns care (improved social welfare, facility upgrades, staff training and mental health support). Conclusion: While burns care has improved in Ghana, there are clear opportunities for improvement. A move towards more integrated care, the development of locally adapted protocols, better financial support, and enhanced caregiver education are essential next steps in elevating the quality of paediatric burn management in Ghana.